Menelaah Pengertian Dialog demi Mencapai Dialog Kehidupan - Pabayo, Ricky Setiawan; Endi, Yohanes; Raharso, Alphonsus Tjatur (Jurnal Teologi Berita Hidup, 2024)
The main focus of this discussion is to examine the attitude of Saint Francis of Assisi and Sultan Malik al-Kamil in building tolerance between religions, especially in West Borneo. St. Francis of Assisi's concern for the war that claimed so many lives at that time, made him feel that humans had begun to forget the social value of other people's lives so that an attitude of mutual suspicion arose within themselves to bring each other down through their religious beliefs. Religion is a personal human affair with God, not a human affair that interferes with the affairs of other human beings with the God they believe in. Therefore, if there is someone who interferes in such matters, a different ideological understanding will emerge. The government is trying to promote a prosperous life by daring to accept the differences that exist in Indonesia. The interreligious dialogue that was created aims to provide answers to the problems that occur to create peace. The goal to be achieved from this research is to build a lively dialogue that overrides religious ideology that leads to acts of tolerance towards others. Therefore, it is necessary for the Indonesian people to first understand what is meant by dialogue. Dialogue is understood as an artistic value in understanding when discussing the meaning, when someone conveys something, it is hoped that it will be responded with sympathy for the other person. If this is not done, then the dialogue is only limited to ordinary discussions or only to dispel suspicions. The novelty of this research is to examine and reflect on the attitude of the meeting of Saints and Sultans in building peace in maintaining the value of life in humans, which at this time has also begun to be forgotten due to differences.